If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -41 = 5x + -1 Reorder the terms: -41 + 11x = 5x + -1 Reorder the terms: -41 + 11x = -1 + 5x Solving -41 + 11x = -1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -41 + 11x + -5x = -1 + 5x + -5x Combine like terms: 11x + -5x = 6x -41 + 6x = -1 + 5x + -5x Combine like terms: 5x + -5x = 0 -41 + 6x = -1 + 0 -41 + 6x = -1 Add '41' to each side of the equation. -41 + 41 + 6x = -1 + 41 Combine like terms: -41 + 41 = 0 0 + 6x = -1 + 41 6x = -1 + 41 Combine like terms: -1 + 41 = 40 6x = 40 Divide each side by '6'. x = 6.666666667 Simplifying x = 6.666666667
| 4-3(3+7a)=-131 | | 1.75x+x=77 | | 3+4i/5+i | | 17=x/12-31 | | 29=7x-6 | | 7=m | | y/5=-2/10 | | (4b-5c)+(5a+2b)= | | w/22+22=44 | | -3(5n-5)=-5n-15 | | x^4+x^3-23x^2+3x+90=0 | | A=7B+5C | | -2=r-(5) | | z/2=z+1/3 | | -3-5/-4+(2-1) | | 4x=238 | | 72+5=9z+3 | | (6x^2+5x+7)-(2x^2-11x+12)= | | 15p/2+p=17 | | -2y=-x+2 | | 6000(1+0.07)9= | | y=1/3x+2/5 | | 8=x-(1) | | 1/5(x+3)^2-5=0 | | -3/20x=6 | | x+4y=-5 | | -4x-4=5-(7x-6) | | 5y^2-y-1=0 | | x+(x-17.8)=196.8 | | 4x/9-5=x | | 5x+5-2x=3+4 | | x-(-4x)=x+9 |